English and Asia - Normala Othman , Subramaniam Govindasamy (2009)
Currently, the dominance in use of English for professional, educational and business is unprecedented in the history of Asia. This growth in use has been ushered in by the pre-eminence of English in a globalized world. Given this scenario, how are Asian languages and cultures facing challenges and seeking accommodation? This book, based on papers written for the Conference English and Asia, explores some of the synergies and turbulence that are thronging Asia in the educational and cultural arena. Among the major themes, one is that of how emerging societies are surging ahead in developing their own resources for teaching and learning English. Many of the papers are in response to this central theme. The meeting of literatures offers another area of scrutiny. Conflicts and turbulence is also explored in some of the papers, especially those concerned with discourse and identity.